Achieving gains in state and local child safety systems and workforce development: application of the framework for quality improvement and innovation in child safety. Issue 6 (4th May 2022) - Leonardo, Jennifer B; Ali, Bina; Stern-Carusone, Jenny; Katradis, Maria
Abstract : Objective: This study investigated the application of the Children's Safety Network (CSN) Framework for Quality Improvement and Innovation in Child Safety through the Child Safety Learning Collaborative (CSLC). Methods: The CSN Framework was used by 26 state/jurisdiction teams that participated in cohort 1 of the CSLC, from November 2018 to April 2020. The aim was to strengthen child safety systems and the workforce to spread child safety evidence-based and evidence-informed strategies and programmes for children and adolescents ages <1–19 years. Procedures: Participating teams' child safety system development, workforce development, engagement in the CSLC, challenges encountered and overall satisfaction with the CSLC were assessed through ongoing CSLC participation records and an end-of-cohort survey (survey response rate: 73.1%). Results: Teams showed an average change of 2.4-fold increase in the spread of evidence-based and evidence-informed child safety strategies and programmes, indicating improvement in child safety systems. Knowledge development on CSLC tools and strategies was reported by 77.8% of teams, with 55.5% reporting CSLC tools and strategies contributed to workforce development. Over two-thirds (70.6%) reported being satisfied or very satisfied with the CSLC, but identified some challenges, including staff turnover and the need to strengthen partnerships. All teams demonstrated engagement in the CSLC, based on participation in a virtual meeting, learning session or a monthly report submission. Conclusions: Despite challenges, teams continued to participate in the CSLC, recognising the importance of collaborative learning. The CSN Framework is helpful for state/jurisdiction teams to improve child safety systems and develop their workforce.